2011
DOI: 10.1097/qai.0b013e3182185276
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Selectively Regulates Production of Inflammatory Cytokines and Shifts the IL-12/IL-10 Balance in Human Primary Cells

Abstract: Our data suggest divergent effects of tenofovir and AZT on proinflammatory responses in monocytes (CCL3 and IL-8) and PBMCs (CCL3). Moreover, tenofovir shifts the IL-10/IL-12 balance after cell stimulation with TLR ligands or infection with live bacteria, thus suggesting that the choice of nucleoside reverse transcriptase inhibitor affects overall inflammation and early immune responses against secondary pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 54 publications
5
65
1
Order By: Relevance
“…16 In the present study, we found that topical TFV treatment altered the vaginal cytokine-profile at 48 h after HSV-2 infection compared to controls (Fig. 4).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…16 In the present study, we found that topical TFV treatment altered the vaginal cytokine-profile at 48 h after HSV-2 infection compared to controls (Fig. 4).…”
mentioning
confidence: 54%
“…[13][14][15] We have previously shown that in human primary PBMCs TDF reduced IL-10 secretion, enhanced IL-12 secretion, and decreased proinflammatory cytokine secretion in response to a bacterial or viral infection or to the stimulation of innate, pathogen-sensing, toll-like receptors. 16 In the present study, we hypothesized that an anti-HSV-2 effect of vaginally applied TFV could be verified in a vaginal challenge mouse model. The study design was similar to that used in the CAPRISA 004 study with application of TFV once before and once after virus challenge.…”
Section: Introductionmentioning
confidence: 99%
“…35 Using paired t-tests, some rectal-secretion cytokines (IL-1b, TNFa, IL-6, MIP-1a; all often classified as ''pro-inflammatory'' were shown to be reduced in the TFV-treated groups at different study stages. Given the small sample size it is of interest that when using the uncorrected cytokine results, all the subjects with reduced ex vivo infectibility at the end of the 7-day exposure period also expressed generally reduced mucosal cytokine levels (above).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TFV and other reverse transcriptase inhibitors (RTI) have been shown to modulate serum and cervical vaginal lavage cytokines and chemokines, as well as the response of immune cells from peripheral blood in humans and mice (19)(20)(21)(22). Overall, these results show that RTI differ in their effects on immune responses.…”
mentioning
confidence: 56%